THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE EMPIRICAL STUDY OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2018 – 2022 - Ambita Adyanning Putri; Sri Laksmi Pardanawati; Hadi Samanto (Jurnal Akuntansi dan Pajak, 2024)
This study aims to determine the influence between the board of directors, board of commissioners, and audit committee on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange. The analysis method used is multiple linear regression. The sample in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. To determine the sample used purposive sampling method. 42 manufacturing companies were obtained which will be used as samples in this study. The results of hypothesis testing in this study, show that the size of the board of directors and audit committee has a significant effect on the financial performance of manufacturing companies. The results of this study also show that the board of commissioners does not have a significant effect on the company's performance.